Carp Edema Virus Infection Is Associated With Severe Metabolic Disturbance in Fish - Pikula, Jiri; Pojezdal, Lubomir; Papezikova, Ivana; Minarova, Hana; Mikulikova, Ivana; Bandouchova, Hana; Blahova, Jana; Bednarska, Małgorzata; Mares, Jan; Palikova, Miroslava (Frontiers in Veterinary Science, 2021)
Significant mortalities associated with emerging viral diseases are challenging the economy of common carp aquaculture. As such, there is an increased need to disentangle how infected fish cope with progressive disease pathology and lose the ability for homeostatic maintenance of key physiological parameters. A natural carp edema virus (CEV) infection outbreak at a carp fish farm provided an opportunity to examine diseased and healthy carp in the same storage pond, thereby contributing to our better understanding of CEV disease pathophysiology. The disease status of fish was determined using PCR-based virus identification combined with analysis of gill pathology. Compared with healthy control carp, the blood chemistry profile of CEV-infected fish revealed major disruptions in electrolyte and acid-base balance (i.e. hyponatraemia, hypochloraemia, hyperphosphatemia, elevated pH, base excess and anion gap and decreased partial dissolved carbon dioxide). In addition, we recorded hyperproteinaemia, hyperalbuminaemia, hypotonic dehydration, endogenous hyperammonaemia and decreased lactate along with increased creatinine, alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase. Red blood cell associated haematology variables were also elevated. The multivariate pattern of responses for blood chemistry variables (driven by sodium, pH, partial dissolved carbon dioxide, ammonia and albumin in the principal component analysis) clearly discriminated between CEV-infected and control carp. To conclude, we show that CEV infection in carp exerts complex adverse effects and results in severe metabolic disturbance due to the impaired gill respiratory and excretory functioning.